Structural, Magnetic, Dielectric, Electrical, Optical and Thermal Properties of Nanocrystalline Materials: Synthesis, Characterization and Application - Yadav, Raghvendra Singh; Anju, Anju; Nisar, Kottakkaran Sooppy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of the research articles and review article, published in special issue "Structural, Magnetic, Dielectric, Electrical, Optical and Thermal Properties of Nanocrystalline Materials: Synthesis, Characterization and Application".